2016
DOI: 10.1007/s10551-016-3093-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Trust Between Leader and Subordinate and Employee Outcomes

Abstract: Stable and enduring cooperative relationships among people are primarily based on mutual trust. However, little evidence exists about the effects of mutual trust between supervisor and subordinate on work outcomes. To understand better the dynamics of trust in supervisorsubordinate relationships, we examined how mutual trust between supervisor and subordinate is associated with work outcomes. Based on a sample of 247 subordinate-supervisor pairs, multilevel analyses revealed a positive effect of perceived mutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 53 publications
(94 reference statements)
0
48
0
Order By: Relevance
“…On the other hand, Jing et al (2014) provided empirical evidence showing that high levels of trust between leader and followers and enhanced financial performance were positively related, as this increases collaboration and strengthens the ability to confront performance problems, and also reduces friction in organizational relationships and the need for controls (such as rules and monitoring), thus leaving time for other activities. Other studies (i.e., Cheung, Wong, & Yuan, 2017;Kim, Wang, & Chen, 2018) have also recently confirmed that leader-follower trust increases job performance. In sum, empirical analysis of the role of leader-follower trust in performance is a nascent and under-explored area of research.…”
Section: Leader-follower Trust and Performancementioning
confidence: 76%
“…On the other hand, Jing et al (2014) provided empirical evidence showing that high levels of trust between leader and followers and enhanced financial performance were positively related, as this increases collaboration and strengthens the ability to confront performance problems, and also reduces friction in organizational relationships and the need for controls (such as rules and monitoring), thus leaving time for other activities. Other studies (i.e., Cheung, Wong, & Yuan, 2017;Kim, Wang, & Chen, 2018) have also recently confirmed that leader-follower trust increases job performance. In sum, empirical analysis of the role of leader-follower trust in performance is a nascent and under-explored area of research.…”
Section: Leader-follower Trust and Performancementioning
confidence: 76%
“…Following Singer and Willett's (2003) recommendation, we spaced the waves of data collection in such a way as to capture the meaning of measured variables during these determined periods of time. Recent research provides evidence that the 2 weeks allows for forming and developing perceptions of our variable of interest (e.g., Fulmer and Ostroff, 2017;Liu et al, 2017;Kim et al, 2018). In addition, based on our discussions with senior management, 2-week lag between every wave of the survey could synchronize with the weekly or 2-weekly employees' regular meetings.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…By contrast, individuals who perceive their relationships with their supervisors as supportive tend to not regard voicing upward as risk-taking and this perception enables them to engage more frequently in voice behavior. Moreover, studies have found that employees who are trusted by their supervisors are more prone to exhibit more citizenship behavior (Lau et al, 2014;Kim et al, 2018). Taking these factors into consideration, we proposed Hypothesis 1 as follows:…”
Section: A Planned Behavior Perspective On Voicementioning
confidence: 99%
“…The current work considers the supervisor's trust from a subordinate's perspective, specifically in terms of the extent of "felt trust" that subordinates believe the leader has for them (Brower, Schoorman, & Tan, 2000;Lau, Liu, & Fu, 2007). Our focus is the process through which followers' felt trust affects their in-role and extra-role job performance (outcomes which have also been a prior concern of felt trust research, e.g., Kim, Wang, & Chen, 2018;Lau, Lam, & Wen, 2014;Salamon & Robinson, 2008).…”
Section: Introductionmentioning
confidence: 99%